Fatigue After Stroke Educational Recovery Program: A Prospective, Phase III, Randomized Controlled Trial - Jones, Kelly; Krishnamurthi, Rita; Barker-Collo, Suzanne; De Silva, Sulekha; Henry, Nathan; Zeng, Irene; Vorster, Anja; Te Ao, Braden; Green, Geoff; Ratnasabapathy, Yogini; Feigin, Valery (Wiley, 2024)
BACKGROUND: Poststroke fatigue affects ≈50% of patients with stroke, causing significant personal, societal, and economic burden. In the FASTER (Fatigue After Stroke Educational Recovery) study, we assessed a group-based educational intervention for poststroke fatigue. METHODS AND RESULTS: Two hundred patients with clinically significant fatigue were included and randomized to either a general stroke education control or fatigue management group (FMG) intervention and assessed at baseline, 6 weeks, and 3 months. The FMG involved weekly psychoeducation sessions over 6 weeks. Coprimary outcomes were the Fatigue Severity Scale and Multidimensional Fatigue Inventory-20 total scores. Adjusted mean total Fatigue Severity Scale scores at 6 weeks (primary end point) were nearly identical for the education control and FMG groups. The adjusted mean difference between treatment groups was -0.13 (SE, 1.4; P=0.92) at 6 weeks and 1.67 (SE, 1.4; P=0.26) at 3 months. Although there were no significant effects, Fatigue Severity Scale outcomes were in the direction of a treatment effect based on the estimated change. Adjusted mean total Multidimensional Fatigue Inventory-20 scores at 6 weeks (primary end point) were similar for the education control and FMG groups. The adjusted mean difference between treatment groups was -0.91 (SE, 1.54; P=0.55) at 6 weeks and -1.26 (SE, 1.8; P=0.49) at 3 months. Both groups had similar secondary outcomes (eg, Multidimensional Fatigue Inventory-20 subscales, sleep, pain, mood, quality of life) at 6 weeks and 3 months. CONCLUSIONS: We found no evidence of significant group-level benefits of FMG over and above general stroke education. Educational group-based interventions for poststroke fatigue should continue to be refined and examined, including consideration of potential impacts at an individual level. REGISTRATION: URL: https://www.anzctr.org.au/; UnIque identifier: ACTRN12619000626167.
Keywords: education; fatigue; intervention; stroke; education; fatigue; intervention; stroke; 32 Biomedical and Clinical Sciences; 3201 Cardiovascular Medicine and Haematology; Stroke; Cerebrovascular; Brain Disorders; Behavioral and Social Science; 7.1 Individual care needs; 6.6 Psychological and behavioural; 6.7 Physical; Stroke; 4 Quality Education; 1102 Cardiorespiratory Medicine and Haematology; 3201 Cardiovascular medicine and haematology